A review of the usability aspects of common web page design paradigms / Wan Norizan Wan Hashim - Wan Hashim, Wan Norizan (2006)
This project is 10 define and determine the common design paradigm used when designing a Web page, which is based on the fundamentals principles of UI design. The outcome will be more focused on the success and its benefit of this paradigm in designing a Web page. It also will answer the question how effective and usable the paradigm when designing a Web page so that user can retrieve information or surfing the Website more efficient. As computer technology is being changed, the web design paradigm would change as well. Thus, it will be more interesting if future study could be done to identifY new paradigm in designing a Web site.